Kerangka Fiqh kepenggunaan masakini / Mohd Hapiz Mahaiyadin and Muhammad Rahimi Osman - Mahaiyadin, Mohd Hapiz; Osman, Muhammad Rahimi (Academy of Contemporary Islamic Studies, 2015)
This paper discusses some of the important principles that form the framework of fiqh consumerism. It should be used as a basis for regulating all activities that utilise natural resources consisting of animals, plants, liquids, minerals, chemicals and microorganisms. The framework reveals the categories of lawful and unlawful sources and emphasises the importance of ihtiyat (careful and coutious) in the use of dubious sources. Rulings relating to the permissibility of consuming unlawful sources in the state of emergency (dharurah) is also elaborated to highlight the beauty of fiqh in solving any difficulty that inflicts one's life. In other words, the paper emphasises that rulings on fiqh consumerism as discussed and deduced by the fuqaha' would apparently bring facilities and easiness to people. They are indeed in conformity to the maqasid al-shariah (objectives of shariah) that safeguards the essential qualities of human life comprising of religion, soul, lineage, intellect and property.